Brain morphometry on congenital hand deformities based on Teichmüller space theory. (January 2015) - Peng, Hao; Wang, Xu; Duan, Ye; Frey, Scott H.; Gu, Xianfeng
Abstract: Congenital Hand Deformities (CHD) usually occurred between the fourth and the eighth week after the embryo is formed. Failure of the transformation from arm bud cells to upper limb can lead to an abnormal appearing/functioning upper extremity which is presented at birth. Some causes are linked to genetics while others are affected by the environment, and the rest have remained unknown. CHD patients develop prehension through the use of their hands, which affects the brain as time passes. In recent years, CHD have gained increasing attention and researches have been conducted on CHD, both surgically and psychologically. However, the impacts of CHD on the brain structure are not well-understood so far. Here, we propose a novel approach to apply Teichmüller space theory and conformal welding method to study brain morphometry in CHD patients. Conformal welding signature reflects the geometric relations among different functional areas on the cortex surface, which is intrinsic to the Riemannian metric, invariant under conformal deformation, and encodes complete information of the functional area boundaries. The computational algorithm is based on discrete surface Ricci flow, which has theoretic guarantees for the existence and uniqueness of the solutions. In practice, discrete Ricci flow is equivalent to a convex optimization problem, therefore has high numerically stability. In this paper, we compute the signatures of contours on general 3D surfaces with the surface Ricci flow method, which encodes both global and local surface contour information. Then we evaluated the signatures of pre-central and post-central gyrus on healthy control and CHD subjects for analyzing brain cortical morphometry. Preliminary experimental results from 3D MRI data of CHD/control data demonstrate the effectiveness of our method. The statistical comparison between left and right brain gives us a better understanding on brain morphometry of subjects with Congenital Hand Deformities, in particular, missing the distal part of the upper limb. Highlights: We propose a novel Teichmüller space theory approach to study brain morphometry. Conformal welding signature reflects the geometric relations of different regions. The invertible method encodes complete information of the functional area boundaries. We evaluate signatures of pre-central and post-central gyrus on subjects and control. Congenital Hand Deformities may make a greater impact on post-central gyrus.